Electrolyte composition and lithium metal battery comprising same
By using borate-pyran electrolytes in lithium metal batteries and using complexes of boron fluoride-based lithium salt and cyclic ether-based solvents, the problem of insufficient cycle life of lithium metal batteries is solved, and efficient lithium deposition and long cycle life are achieved.
Patent Information
- Application Number
- CN202380061335.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-08
- Filing Date
- 2023-08-21
- Publication Date
- 2025-03-21
AI Technical Summary
There is a technical gap in the cycle life of lithium metal batteries, mainly due to the corrosion between liquid electrolyte and lithium, which reduces the Coulomb efficiency and the large electrolytic mass, which limits the cycle life.
Borate-pyran-based electrolyte is used to form a complex through boron fluoride-based lithium salt and cyclic ether-based solvent to form a low-corrosive boron fluoride-cyclic ether-based electrolyte, and the lithium electrolyte interface is finely passivated by the LiF reconstruction process.
Lithium metal batteries that work for a long time at low N/P and E/C ratios are achieved, which significantly improves the uniformity of lithium deposition form and lithium plating/peeling efficiency, and extends the cycle life of the battery.
Smart Images

Figure CN119678286A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0105317 filed on August 23, 2022, in the Korean Intellectual Property Office, and Korean Patent Application No. 10-2023-0103596 filed on August 8, 2023, in the Korean Intellectual Property Office, the disclosures of which are incorporated herein by reference in their entireties.
[0003] The present disclosure relates to electrolyte compositions and lithium metal batteries containing the same. Background Art
[0004] Lithium (Li) metal is the most promising negative electrode material for next-generation batteries. When Li metal is electrodeposited on a general organic solvent together with a lithium salt, it forms a three-dimensional microstructure with a large surface area and reacts with a liquid electrolyte to form a SEI (solid electrolyte interface). However, recent reports have shown that the plating / stripping process of Li metal induces the continuous disintegration and regeneration of SEI and the formation of inert Li, which leads to battery failure.
[0005] Basically, in order to control the morphology of lithium metal precipitates in electrolyte design, a strategy of forming a specific SEI phase through the decomposition of electrolyte species is adopted, and this specific SEI phase is considered to be useful for the reversibility of lithium. In previous studies, it is known that increasing Li2O, LiF, Li2S, and LiN x O y The content of crystalline or organic materials with excellent physicochemical properties has a positive impact on the stability of SEI and thus the reversibility of Li metal anode.
[0006] Therefore, many researchers continue to focus on the addition of additives that react favorably with Li to form a stable SEI, or dissolution engineering (highly concentrated electrolytes (HCEs), locally highly concentrated electrolytes (LHCEs), and electrolytes using fluorinated solvents) to promote this reaction.
[0007] However, a large number of SEI materials proposed in such studies to extend the life of lithium metal batteries (LMBs) suffer from the following problems: high coulombic efficiency (CE) electrolytes lead to Li+ loss instead of forming inert Li3, which affects the formation of SEI.
[0008] In fact, compared with recent all-solid-state batteries, LMBs based on liquid electrolytes have a technological gap in cycle life, which seems to be due to the corrosion between the liquid electrolyte and Li3, which reduces the Coulombic efficiency in LMBs. In addition, lithium metal batteries have a higher cycle life than those based on traditional anode chemistries (e.g., graphite or silicon anodes, ~1.5 g Ah). -1 ) batteries with much larger electrolyte volumes (>2.4 g Ah -1 ) work, which consumes the electrolyte and thus limits the cycle life. In addition, recently developed electrolytes have similar or worse schedule characteristics than previous electrolytes, and the performance is still insufficient for use in electric vehicles that must travel for a long time (e.g., more than 10 years).
[0009] Therefore, the morphological uniformity of the electrodeposited lithium can be improved by making the Li + Minimizing the loss of electrolyte and the formation of SEI is considered to be an urgent problem to be solved in this technical field. Summary of the invention
[0010] Technical issues
[0011] In this regard, the embodiments according to the present disclosure show the possibility of solving the problem of high-density lithium morphology of lithium metal anode by controlling the liquid electrolyte, but there is a problem of lithium loss due to lithium corrosion with the liquid electrolyte. Therefore, the inventors attempted to apply a borate-pyran electrolyte to solve the limitation of conventional liquid electrolyte LMB having a lithium electrolyte corrosion problem.
[0012] Technical Solution
[0013] Hereinafter, an electrolyte composition for a lithium metal battery according to a specific embodiment of the present disclosure will be described.
[0014] The terms or words used in the specification and the appended claims should not be construed as limited to the ordinary meaning or dictionary meaning, and the present disclosure should be interpreted with the meaning and concept consistent with the technical idea of the present disclosure based on the principle that inventors can appropriately define the concepts of the terms to appropriately describe their own inventions in the best manner.
[0015] The terms used herein are provided to describe exemplary embodiments but do not limit the concepts of the present invention. Unless the context clearly indicates otherwise, a singular form includes a plural form.
[0016] It should be understood that the terms "including", "comprising", "having" and the like are used herein to indicate the presence of stated features, numbers, steps, components or a combination thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, components or a combination thereof.
[0017] Electrolyte composition
[0018] According to one embodiment of the present disclosure, an electrolyte composition is provided, comprising: an ether solvent having an ether group; and a boron fluoride lithium salt or a non-boron fluoride lithium salt dissolved in the ether solvent, wherein the boron fluoride lithium salt or the non-boron fluoride lithium salt forms a complex with the ether solvent. The electrolyte composition may be an electrolyte composition for a lithium metal battery.
[0019] Specifically, the ether-based solvent may be a cyclic ether-based solvent, and the ether-based solvent may have one ether group.
[0020] The electrolyte composition can be specifically a boron fluoride-cyclic ether electrolyte, wherein the boron fluoride-cyclic ether electrolyte has low corrosiveness and can finely passivate the lithium electrolyte interface through LiF reconstruction, thereby minimizing the Coulomb ineffectiveness of SEI formation in lithium. In addition, the boron fluoride-cyclic ether electrolyte can exhibit ideal lithium deposition and high lithium plating / stripping efficiency, and can meet the conditions required for long-term operation of LMB at low N / P and E / C ratios.
[0021] In exemplary embodiments, the boron fluoride-based lithium salt may include a boron fluoride-based lithium salt of Formula 1 below.
[0022] [Formula 1]
[0023] LiBF x R y
[0024] Where R is -CF3 or -styrene, and x+y=4
[0025] In an exemplary embodiment, the non-fluorinated boron-based lithium salt may include an anion-based lithium salt having a Group 13 element as a central atom, or a lithium salt consisting of a boron central atom and a halide-based anion other than fluorine. For example, the anion-based lithium salt having a Group 13 element as a central atom may include LiAlF4, LiGaF4, etc.
[0026] In an exemplary embodiment, the ether solvent may include at least one solvent selected from the group consisting of tetrahydrofuran (THF), tetrahydropyran (THP), furan, pyran, ethylene oxide, oxetane, oxepane and dioxane. Specifically, tetrahydrofuran (THF) and tetrahydropyran (THP) can be cyclic ether solvents in which functional groups are added to cyclic ethers, furan and pyran can be unsaturated cyclic ether solvents containing partial double bonds, ethylene oxide, oxetane and oxepane can be triangular, quadrilateral and heptagonal cyclic ether solvents, respectively, and dioxane can be a solvent containing multiple ether groups. For example, tetrahydropyran (THP), tetrahydrofuran (THF) and diethyl ether (DEE) having an ether group and a functional group added to the cyclic ether can have a significantly lower reduction potential than other solvent molecules. However, in the case of linear molecules such as DEE, due to Li + The binding energy is relatively low, and coordination of anions may be promoted, and thus this may be disadvantageous. On the other hand, THP has a relatively high boiling point compared to THF, and thus may be chemically stable as a six-membered ring, and thus may be more preferred.
[0027] In an exemplary embodiment, the boron fluoride lithium salt may be LiBF4, and the ether solvent may be tetrahydropyran (THP). In the case of a lithium salt and a solvent combination, a boron trifluoride-ether complex may be formed to form a uniform SEI structure.
[0028] In an exemplary embodiment, the electrolyte composition may further include at least one selected from the group consisting of an ion-conductive lithium salt and an additive. Specifically, the ion-conductive lithium salt may include at least one lithium salt selected from the group consisting of LiPF6, LiDFOB, LiBOB, LiTf, LiBETI, LiCTFSI, LiTFSI, LiNO3, LiFSI, LiAsF6, LiClO4 and LiSbF6. In addition, the additive may include at least one selected from a lithium salt containing -F (e.g., LiDFOB, LiFSI) and a solvent containing -F (e.g., FEC, DFEC, TFEC, TTE, TFTFE, TFOFE, BTFE, OFE) acting as a LiF forming agent. Preferably, the ion-conductive lithium salt is LiTFSI, and the additive may be FEC used as a LiF forming agent.
[0029] In an exemplary embodiment, the anion of the ion-conductive lithium salt may have a lower Li + Therefore, the anions of the boron fluoride lithium salt and THP mainly bind to the Li +interact with each other, while the anions of the ion-conductive lithium salt and the LiF-forming agent may exist mainly as free molecules.
[0030] In an exemplary embodiment, the electrolyte composition may have a BO stretching signal and a FBF bending signal in SERS analysis. Specifically, during potential strengthening, about 490 cm -1 and about 1350cm -1 A pair of peaks nearby gradually intensified, which can correspond to the BO stretching signal and the FBF bending signal, respectively. Therefore, it can be confirmed that BF3 and the ether group have been complexed with the THP molecules.
[0031] Lithium Metal Batteries
[0032] In another embodiment of the present disclosure, a lithium metal battery is provided, comprising: the above-mentioned electrolyte composition; a negative electrode comprising a lithium metal thin film formed on a negative electrode current collector; a positive electrode comprising a positive electrode active material layer formed on a positive electrode current collector; and a separator formed between the negative electrode and the positive electrode.
[0033] In an exemplary embodiment, the boron fluoride lithium salt or the non-boron fluoride lithium salt and the cyclic ether-based solvent may form a complex on the surface of the lithium metal thin film, for example, boron fluoride and the ether-based solvent may form a boron trifluoride-ether complex.
[0034] In an exemplary embodiment, the lithium metal battery may further include an SEI layer formed on the lithium metal film, wherein the SEI layer may have only a signal of a LiF (111) or LiF (220) grid in a fast Fourier transform (FFT) image. On the other hand, the SEI layer may not contain S, N, and B elements. In particular, the absence of S, N, and B elements in the SEI layer may mean that LiF is formed by FEC instead of BF4. - or TFSI - is formed by defluorination reaction.
[0035] In an exemplary embodiment, the SEI layer may be formed by a reconstruction process. Specifically, BF3-THP is formed on the surface of the lithium metal film, LiF is precipitated on Li0, and BF3-THP reacts with the initial LiF particles to convert back to LiBF4. LiBF4 may repeat the process of forming BF3-THP while precipitating LiF again at the sites exposed by Li0, thereby passivating the Li surface with fine LiF crystals.
[0036] Beneficial Effects
[0037] Embodiments of the present disclosure provide a boron fluoride-cyclic ether electrolyte as an electrolyte composition for a lithium metal battery. The boron fluoride-cyclic ether electrolyte has high reduction stability and finely passivates the lithium electrolyte interface through the LiF reconstruction process, and minimizes the dendrite-free lithium form and Coulomb ineffectiveness to enable the formation of a lithium electrolyte interface.
[0038] In addition, in an embodiment of the present disclosure, a boron fluoride-cyclic ether liquid electrolyte Li||LiNi is provided. 0.8 Co 0.1 Mn 0.1 O2 (NCM811) pouch cells with limited electrolyte / anode capacity ratio (E / C, 1.82 g Ah -1 , energy density 424Wh kg -1 ) has a long cycle life of 500 cycles at 1.18g / Ah -1 (Energy density 456Wh kg -1 ), which corresponds to a value of E / C ratio far exceeding that of the state-of-the-art LMBs reported so far.
[0039] In the design of the electrolyte according to one embodiment of the present disclosure, the intrinsic reactivity of the electrolyte with Li is moderated to improve the reduction stability at the negative electrode-electrolyte interface ( Figure 1a ), which involves the delicate passivation of Li due to the dynamic reconstruction of LiF crystals in the SEI ( Figure 1b ). The borate-pyran electrolyte has the following key functions: the LiF reconstruction process endows the SEI with high uniformity and passivation to delay the consumption of Li and electrolyte, which is even effective at E / C 2gAh -1 It can also be applied to LMB under the conditions of BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1a Figure 2 is a design concept of a borate-pyran-based electrolyte, which schematically shows the electrolyte reduction process at the Li anode.
[0041] Figure 1b The BF3 complexation reaction is shown, which involves electrodeposition of LiF from THP and LiBF4 onto Li0, followed by a BF3-THP reaction where the LiF dissolves and returns to THP and LiBF4, with purple atoms representing BF4 - The atoms involved in the formation of BF3 adducts, the orange and green F represent the F of LiF reconstructed on the Li0 surface and the F of LiF initially formed in SEI, respectively.
[0042] Figure 1c The reduction potentials of various organic solvents and Li+ Binding energy.
[0043] Figure 1d The Li of each anion in the borate-pyran electrolyte is shown. + Dissolution structure distribution and the most dominant structure.
[0044] Figure 1e The primary reduction potentials of the ether electrolyte (4M LiFSI DME) and the borate-pyran electrolyte (0.4M LiBF4 0.4MLiTFSI THP+20%FEC) are shown, where the blue squares represent the anion reduction potential, the red squares represent the solvent reduction potential, and the grey squares represent the reduction potential of the secondary dissolved structures.
[0045] Figure 2a SEI microstructure obtained by cryo-TEM and XPS is shown, which shows the cryo-TEM image of the SEI layer of Li metal during aging in a borate-pyranose electrolyte.
[0046] Figure 2b Single crystalline LiF particles in the SEI of electrodeposited Li and reconstructed LiF in the SEI of aged Li are shown.
[0047] Figure 2c A comparison of the crystal size of inorganic particles in the SEI according to aging time is shown.
[0048] Figure 2d and 2e XPS spectral analysis results of the atomic concentrations of oxygen and fluorine in SEI and curve fitting are shown before (d) and after (e) aging for 12 hours.
[0049] Figure 3a BF3 complexation and LiF dissolution in borate-pyran electrolytes are shown, which show the in situ SERS spectrum (middle), constant current voltage curve (left) and Raman intensity corresponding to the electrolyte components (right) of the borate-pyran electrolyte in the Li||Cu-Ag (SERS substrate) cell during potential decrease, respectively.
[0050] Figure 3b An energy diagram for the complexation reaction of BF3 in LiBF4 is shown.
[0051] Figure 3c The results show the BF3-THF with dissolved LiF salt at various concentrations. 11 B NMR spectrum.
[0052] Figure 3d The normalized values obtained by integrating all peak areas are shown. 11 B Relative intensities of NMR spectra.
[0053] Figure 3e A comparison of the ionic conductivity of LiF solutions with different concentrations in different types of solvents is shown.
[0054] Figure 3f Schematic illustration of the reconstruction process of SEI in borate-pyran electrolyte.
[0055] Figure 4a is an electrochemical analysis of the liquid electrolyte, which shows a pressurized Li plating setup and a pressure of 290 kPa at 0.5 mA cm -2 Electrodeposition on a Cu current collector at a current density of 2 mAh cm -2 )'s Li form.
[0056] Figure 4b Shown is a comparison of the Coulombic efficiency of Li plating / stripping in Li||Cu cells with different electrolyte configurations.
[0057] Figure 4c The quantification of volume usage during the modified Auerbach method by titration gas chromatography is shown.
[0058] Figure 4d The interfacial resistance and normalized resistance (relative to R at t = 0) of Li||Li coin cells in various electrolytes are shown as a function of time. 界面 ), where the dashed line represents the curve fitted by the empirical power law.
[0059] Figure 4e Shown is the Coulombic efficiency of Li plating / aging / stripping in Li||Cu coin cells over time.
[0060] Figure 4f The average corrosion rate of plated Li during aging is shown.
[0061] Figure 5a Schematic diagram of the Li||NCM811 dual-cell configuration for pouch cell performance analysis.
[0062] Figure 5b Comparison results of the electrolyte volumes of LMBs and LIBs are shown.
[0063] Figure 5c Shown is a comparison of the speed performance of the LMB, where 0.2 C constant current and 4.25 V constant voltage modes were applied during all charging processes.
[0064] Figure 5d and 5e The cycling performance and Coulombic efficiency of the LMB are shown.
[0065] Figure 5f A comparison of the swelling extent of Li||NCM811 bicells using three electrolytes with the same initial cell thickness is shown, where the data for each cycle is calculated by measuring the thickness at multiple locations in one pouch cell.
[0066] Figure 6 a to Figure 6 c shows the (a) MD snapshot at t = 0, (b) RDF, and (c) N(r) in 0.4 M LiBF4 and 0.4 M LiTFSI THP 20%FEC electrolytes, respectively.
[0067] Figure 7 a to Figure 7 d is a MD snapshot showing the ion distribution in each time region in 0.4M LiBF4 0.4M LiTFSI THP 20%FEC electrolyte, which shows the distribution at (a) t = 0 ns, (b) t = 1.67 ns, (c) t = 3.33 ns and (d) t = 5.00 ns, respectively.
[0068] Figure 8 a to Figure 8 c shows (a) MD snapshot at t = 0, (b) RDF, and (c) N(r) in 4 M LiFSI DME electrolyte, respectively.
[0069] Fig. 9 a to Fig. 9 d is a MD snapshot showing the ion distribution in various time regions in 4M LiFSI DME electrolyte, which shows the distribution at (a) t = 0 ns, (b) t = 1.67 ns, (c) t = 3.33 ns and (d) t = 5.00 ns, respectively.
[0070] Fig.10 a to Fig.10 f is the XPS spectrum of the SEI layer, which shows that 1M LiPF6 (a) F1s, (b) O1s, (c) C1s, (d) N1s, (e) S2p and (f) B1s spectra of EC / EMC+2%VC (black spectrum) and 0.4M LiBF40.4M LiTFSI THP 20%FEC (red spectrum).
[0071] Fig.11 a and 11b show the atomic percentage of the SEI layer relative to (a) 1M LiPF6 EC / EMC+2%VC and (b) 0.4M LiBF4 0.4MLiTFSI THP 20%FEC.
[0072] Fig.12a An in-situ Raman cell, which is the in-situ SERS device used in the present disclosure, is schematically shown.
[0073] Figure 12b Shown are SEM images of a lab-made SERS substrate (AgNPs on Cu grid) and a top-view image of an in-situ Raman cell.
[0074] Fig.13a The assignment of peaks by comparing the ex situ Raman spectrum of the 0.4M LiBF4 0.4M LiTFSI THP 20%FEC electrolyte with the spectrum of the in situ Raman cell is shown.
[0075] Fig.13b In situ Raman spectra of 0.8M LiTFSI THP 20%FEC electrolyte are shown.
[0076] Fig.14a is a DFT simulation of the BF3 complexation reaction using various solvents, which shows the energy diagram of the BF3 complexation reaction of LiBF4 depending on the organic solvent.
[0077] Fig.14b The optimized molecular structure of BF3 adduct in DFT simulation of BF3 complexation reaction is shown.
[0078] Fig.15 a to Fig.15 d is an optical image of 1M LiF solution, which respectively shows (a) 1M LiF BF3-THP, (b) 1M LiF DME, (c) 1M LiF THF and (d) 1M LiF THP solution.
[0079] Fig.16 It is the XPS spectrum of the SEI layer relative to electrodeposited lithium and aged lithium, which shows (a) F1s, (b) O1s, (c) C1s, (d) N1s, (e) S2p and (f) B1s spectra, where the electrodeposited lithium is the black spectrum and the lithium aged for 12 hours is the red spectrum.
[0080] Fig.17 a and 17b are cryo-TEM images of the SEI layer of Li metal in 0.8 M LiTFSI THP 20% FEC electrolyte during aging, which are (a) time t=0 and (b) time t=12, respectively.
[0081] Fig.18 a to Fig.18c shows the morphology of lithium electrodeposited on (a) 1M LiPF6 EC / EMC 2%VC electrolyte, (b) 1.5M LiFSIDME / TTE electrolyte, and (c) 0.4M LiBF40.4M LiTFSI THP 20%FEC electrolyte.
[0082] Fig.19 a and 19b show the discharge capacity and Coulombic efficiency of the Li||NCM523 full cell, respectively.
[0083] Fig. 20 The ionic conductivity of representative electrolytes is shown.
[0084] Fig.21 21a and 21b show (a) the results of measuring the oxidation stability of various electrolytes in Li||Al batteries using LSV, and (b) an enlarged view of a local area of the result of (a). DETAILED DESCRIPTION
[0085] Hereinafter, various embodiments of the present disclosure will be described in detail with reference to the accompanying drawings so that those skilled in the art can easily perform them. The present disclosure can be modified in various different ways and is not limited to the embodiments set forth herein.
[0086] In the embodiments and comparative examples, 1M LiPF6 EC / EMC (1:1 volume / volume, Phanax) 2%VC (99.5%, Sigma Aldrich) and 1.5M LiFSI (99.9%, Sigma Aldrich) DME (Sigma Aldrich) / TTE (SynQuest Labs) (22:88 volume / volume) were used as control electrolytes. THP (99%), LiBF4 (99.99%) and LiTFSI (99.95%) were purchased from Sigma Aldrich and used, and FEC (98%) was purchased from TCI. The electrolyte compositions of the embodiments and comparative examples were prepared in a glove box filled with argon and had the following composition.
[0087] Example 1: Borate-pyran liquid electrolyte
[0088] A borate-pyran-based liquid electrolyte was prepared by mixing 0.4 M LiBF 4 as a borofluoride lithium salt, 0.4 M LiTFSI as an ion-conductive lithium salt, and 8:2 volume / volume THP / FEC as a solvent.
[0089] Comparative Example 1: Conventional low-corrosive electrolyte
[0090] The low-corrosive electrolyte was prepared by mixing 1M LiPF6 as lithium boron fluoride salt, 1:1 volume / volume EC / EMC (ethylene carbonate hexafluorophosphate / ethyl methyl carbonate) as a solvent, and 2% VC as an additive.
[0091] Comparative Example 2: Highly Corrosive Electrolyte
[0092] 1 M LiFSI as an ion-conductive lithium salt and 22:78 volume / volume DME / TTE (1,2-dimethoxyethane / 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether) as a solvent were mixed to prepare a highly corrosive electrolyte.
[0093] Manufacturing example: Manufacturing of pouch cells
[0094] The prototype pouch cell was fabricated as follows. A Li anode (40 μm, mixed metal) and a double-sided coated LiNi 0.8 Mn 0.1 Co 0.1 O2 cathode (NMC811, provided by LG New Energy Company, 18.78 mg cm -2 Area loading, active material: Super PC65:PVDF=96:2:2) were punched into sizes of 40mm×60mm and 30mm×50mm respectively. Cu foil and NMC positive electrode were welded to Ni and Al tabs using an ultrasonic welder. All electrodes and separators were stacked and packaged in aluminum bags. The 0.4M LiBF40.4M LiTFSI THP / FEC of Example 1 was heated to 200μl (1.92 g Ah -1 ) or 130 μl (1.24 g Ah -1 ) injection to fabricate Li||NCM811 pouch cells. All battery assembly processes were carried out in an argon-filled glove box.
[0095] Experimental methods
[0096] Li morphology and SEI properties
[0097] SEM analysis was performed using a field emission scanning electron microscope (FE-SEM, Sirion, FEI Company). Electrodeposited Li (0.5 mA cm -2 and 2mAh cm -2 ) and surface cleaning was performed at 5 kV to remove the damaged layer caused by Ga ions.
[0098] The composition of the SEI was analyzed by in situ X-ray photoelectron spectroscopy (Axis-Supra, Kratos Corporation) using Al X-rays (hν=1486.7 eV).
[0099] Cryo-TEM
[0100] Cryo-TEM analysis was performed using a 200 kV transmission electron microscope (TEM, Glacios, Thermo Fisher Scientific) and the microstructure of the SEI electrodeposited on Li was observed while minimizing the reaction with air and damage from the beam. -2 and 1mAh cm -2 ) were placed in a microtube (Eppendorf) in an argon-filled glove box, then taken out and immediately placed in liquid nitrogen. The sample was then transferred to the TEM instrument via an automatic loader capsule and cassette system while completely immersed in liquid nitrogen.
[0101] NMR: 400ul DMSO (200ul Ely + 1.2 ml DME) → 400ul solution + 1ml DME
[0102] In situ SERS
[0103] An in-situ Raman cell (EQ-STC-RAMAN, MTI) was used to detect the BF3 adducts formed on the negative electrode surface. As a SERS substrate, the preparation and use of the Ag-Cu grid are as follows. The 200-mesh Cu grid was immersed in a 5mmol AgNO3 aqueous solution for 2 minutes, and the Cu-Ag grid that had undergone galvanic exchange of Cu and Ag was washed several times with deionized water. After vacuum drying for one day, the in-situ Raman cell was assembled in an argon-filled glove box. The Raman signal was measured by applying a 514 nm laser with an acquisition time of 60 seconds.
[0104] Electrochemical experiments
[0105] For electrochemical measurements, 2032-type coin cells containing 50 μl of electrolyte were used.
[0106] The average CE was measured according to the following standard protocol: (1) -2 Electrodeposition of 5 mAh cm on Cu at a current density of -2 of Li and stripping at 1.0 V; (2) at 0.5 mA cm -2 Electrodeposition of 5 mAh cm on Cu at a current density of -2 of Li; (3) at 0.5 mA cm-2 Repeated plating / stripping at a current density of 1 mAh cm -2 of Li for 10 cycles; and (4) all Li was stripped to 1.0 V. Prior to CE measurements, the Li||Cu cells were kept at 0 V for 24 h before cycling to allow SEI to form on the Cu substrate.
[0107] LSV, ionic conductivity and R 界面 Measured using a Solartron 1470E frequency response analyzer.
[0108] EIS was performed in the frequency range from 1 MHz to 0.1 Hz with a perturbation level of 10 mV.
[0109] Li||NCM523 coin cell test is performed by using LiNi 0.5 Mn 0.3 Co 0.2 O2 cathode (NCM532, 21.47 mg cm -2 Area loading, NCM523:Super P C65:PVDF =94:3:3), 40μm Li negative electrode, PE separator (Asahi, 19μm).
[0110] During the work of the Li||NCM811 pouch cell of the fabrication example, a clamping torque was applied using a pressure fixture with a 1 mm silicon pad to uniformly pressurize. The initial pressure was 286 kPa. For battery testing, a WBCS3000 L battery tester was used at 25 °C. All battery assembly processes were carried out in an argon-filled glove box.
[0111] DFT calculations
[0112] Density functional theory calculations (DFT) were performed using the program package Dmol3 (Accerlrys) of Materials Studio. In Dmol3, numerical orbitals were used as basis functions, where each orbital corresponds to an atomic orbital. In addition, a dual numerical plus polarization (DNP) function and a global orbital cutoff of 4 Å were used.
[0113] DFT calculations were performed using a gradient-corrected (GGA) functional with the Perdew-Bueke-Ernzerhof (PBE) exchange-correlation functional. dmol3-PBE COSMO calculations were applied to the solvent environment. The tolerances for energy, gradient, and displacement convergence were 0.00001 Hartree / Å, 0.002 Hartree / Å, and 0.005Å, respectively. The force tolerance for the self-consistent field (SCF) cycle was 1.0 × 10 -6The DFT-D2 method in the figure is used to describe the van der Waals interaction (vdW), and the method is optimized for several DFT functions.
[0114] Li was calculated using the following formula 1 + Primary molten coating (E red )'s reduction potential.
[0115] [Formula 1]
[0116]
[0117] in and are the free energies of reduction and dissolution of the initial complex in the gas phase at 0 K, respectively, and and is reduced at 0 K and the initial Li + of free energy.
[0118] MD calculation
[0119] Molecular dynamics calculations were performed using the Forcite package of Materials Studio (Accerlrys, Inc.). All building blocks were constructed in the simulation cell by geometry optimization and charges were applied by DFT.
[0120] MD was performed using the Forcite module and Forcefield COMPASS III. 0.4MLiBF4 0.4M LiTFSI THP 20% FEC (16 Li + ,8 BF4 - 、8 TFSI - MD simulations were performed using a 0.001 kcal mol -1 Å -1 An intelligent algorithm with convergence tolerance is used to geometrically stabilize the system.
[0121] The system was then equilibrated in the 1 ns NPT and 1 ns NVT ensembles using the Nose algorithm with a Q ratio of 0.1. After equilibration, simulation data were collected by sampling at 45 fs time intervals while running a 5 ns NVT with a 1 fs time step.
[0122] The radial distribution function (RDF) was calculated using the following formula 2:
[0123] [Formula 2]
[0124]
[0125] The coordinate number N(r) is calculated using the following formula 3.
[0126] [Formula 3]
[0127]
[0128] Experimental Example 1: Electrolyte Design
[0129] The reduction potential of electrolyte molecules and dissolved complexes has a significant impact on the reduction stability of the entire electrolyte system. Recent studies have confirmed that + The thermodynamic influence of bound electrolyte molecules on the reductive decomposition is much higher than that of free molecules.
[0130] An important goal of the present disclosure is to minimize the reduction in coulombic efficiency due to the reductive decomposition of the electrolyte. To this end, weakly reactive molecules are used instead of highly reactive anions (e.g., FSI) as in conventional HCE or LHCE. - or DFOB - ) as a leading participant in Li + The electrolyte of the dissolved sheath is calculated by density functional theory (DFT, Figure 1c ) studied the reduction potential of various organic solvents and Li + Binding energy. In addition, ether solvents, except for 2-methyltetrahydrofuran (MTHF) and 1,3-dioxolane (DOL), showed lower reduction potentials than carbonates. In particular, tetrahydropyran (THP), tetrahydrofuran (THF), and diethyl ether (DEE) having one ether group were found to have significantly lower reduction potentials than other solvent molecules.
[0131] In the case of DEE, Li + The binding energy is relatively low (0.32 eV), which promotes the coordination of anions, which is contrary to what is pursued in the present invention. On the other hand, cyclic ethers with one ether group, such as tetrahydrofuran (THF) and tetrahydropyran (THP), show good binding properties with Li + The high binding energy of Li is expected to be good for the + Among them, THP has a relatively high boiling point of 88°C compared to THF (boiling point 66°C), and due to its chemical stability as a six-membered ring (the ring strain energy of THP is 0.5 kcal mol -1 , the ring strain energy of THF is 5.9 kcal mol -1 ) was selected as the main solvent.
[0132] This LiBF4 / THP electrolyte combination can induce reconstruction reactions in the SEI, but the ionic conductivity is very low (2.9×10 -6S cm -1 ), and it is relatively stable to Li metal compared to other Li salts with high dissociation. Therefore, LiTFSI was added as an auxiliary salt to impart ionic conductivity to the LiBF4 / THP electrolyte. FEC was added as the initial LiF source for the reconstruction reaction.
[0133] According to the above process, a boron fluoride-cyclic ether electrolyte (0.4 M LiBF4 0.4 M LiTFSI THP 20% FEC) was prepared, and its performance as an electrolyte for lithium metal batteries was studied.
[0134] The dissolution structure of the boron fluoride-cyclic ether electrolyte was studied by molecular dynamics (MD) simulation. The results showed that the ether groups of 3 to 4 THP molecules in the primary solvation sheath were bound to Li + closely interact with other molecules, including TFSI - 、BF4 - and FEC, showing uneven average coordination numbers (0.20, 0.72, and 0.0006, respectively, Figure 6 and Figure 7 ).
[0135] Opposite + Observation of the dissolved structure shows that only 12.2% of BF4 - showed solvent separated ion pairs (SSIP), while 77.4% TFSI - Display SSIP( Figure 1d ). Since FEC has a weak Li + binding energy, so it does not participate in Li + The primary solvation sheath.
[0136] From these results, it can be seen that THP and BF4 - Mainly with Li participating in the first solvation sheath + Interaction, while TFSI - and FEC exist mainly as free molecules.
[0137] On the other hand, the primary Li + The reduction potential of the solvation sheath ( Figure 1e ). When the commonly used LiFSI / DME electrolyte was used as a control, it showed that one or two FSI - Contact ion pairs (CIP) or aggregates (AGG) ( Figure 8 and 9 ).
[0138] As previously reported, the solvation sheath exhibits 1.90 V vs Li / Li +or 2.21V vs Li / Li + It is known that FSI-rich Li + The dissolution structure has a high reduction potential and rapidly decomposes the FSI on the Li surface to form an inorganic-rich SEI.
[0139] In contrast, the Li + The dissolving structure is mainly composed of BF4 - (Li + (THP)3(BF4)1) or SSIP (Li + The contact ion pair (CIP) of (THP)4) has -0.606 V vs Li / Li + or -0.284 V vs Li / Li + In addition, free FEC and free TFSI - Combined with Li + 0.725V vs Li / Li + and 0.402V vs Li / Li + of lower reduction potential.
[0140] On the other hand, nitrogen, sulfur, and boron species (>1% atomic percent) were hardly observed in the SEI formed by the borate-pyran electrolyte. Therefore, it can be confirmed that almost no TFSI occurs. - and BF4 - The reductive decomposition ( Fig.10 and 11 ).
[0141] Experimental Example 2: Analysis of the Reconstruction Response of the Membrane Structure
[0142] The microstructure of the SEI on the Li metal surface in borate-pyran electrolytes was investigated by cryo-transmission electron microscopy (cryo-TEM). Figure 2a ). Only the signals of LiF(111) or LiF(220) grids were observed in the fast Fourier transform (FFT) images.
[0143] Similar to the above results, in the XPS results of the SEI layer, LiF was observed as the most dominant inorganic substance ( Fig.10 and 11 ). In particular, the absence of S, N, and B elements in the SEI layer means that LiF is synthesized through FEC rather than BF4 - or TFSI - is formed by defluorination reaction.
[0144] The SEI on the electrodeposited lithium surface has a mosaic structure observed in conventional carbonate electrolytes. As indicated by the cyan highlights, the LiF species have crystallized and dispersed in specific locations in the SEI. It can be confirmed that the large LiF mosaic structure observed on the electrodeposited Li surface gradually disappears, and after 6 to 12 hours, fine LiF crystals are densely distributed on the SEI. High-magnification TEM images and FFT images provide information about the atomic arrangement of LiF species in the SEI ( Figure 2b ). The single crystal LiF observed in the initial stage was crushed into fine glassy LiF after 12 hours. A short-range structural order of about 2 nm (i.e., several layers of LiF grids) was observed in the atomic image, which resulted in the appearance of LiF 110 signals in the FFT image. As a result of the statistical examination of the crystal size, the average crystal size showed a gradual decrease from the initial 6.5 nm to 2.1 nm ( Figure 2c ). In addition, it was confirmed that the thickness of SEI decreased from 13.3 nm to 9.1 nm with the aging time.
[0145] In the electrolyte without LiBF4 (0.8M LiTFSI THP+20% FEC), no significant changes in the crystallite size or the microstructure of the SEI were observed during aging, which indicated an increase in SEI thickness (Figure 12) and a time dependence of the LiBF4 involvement in the microstructure of the SEI.
[0146] The atomic concentration or bonding state ratio (especially the amount of LiF, Figure 2d and 2e ) shows almost no change, which indicates that the reduction of LiF crystal size in borate-pyran electrolytes is not caused by the irreversible dissolution of LiF into the electrolyte phase.
[0147] The size reduction of LiF crystals and the decrease in SEI thickness observed in cryo-TEM cannot be explained by the typical SEI growth with aging time observed in typical electrolyte systems. Based on this, it can be expected that LiF reconstruction will occur in boron fluoride-cyclic ether electrolytes.
[0148] To confirm the time-dependent evolution of the SEI microstructure in borate-pyran-based electrolytes, the chemical nature of THP relative to LiBF4 and Li was investigated.
[0149] from( Figure 3a , Figure 13), THP, FEC, and LiTFSI (each at 817 cm -1 、732 cm -1 and 741 cm-1 , Fig.14a ) signal. LiBF4 - The signal is difficult to detect because BF4 - The Raman scattering signal may be - The fluorescence signal is blocked.
[0150] When the potential is decreased (i.e., asymptotically isopotential with the Li surface), a pair of new peaks (~490 cm -1 and ~1350cm -1 ) gradually increases, which may correspond to the FBF bending in the BF3 and BO stretching mode. From the FBF bending of BF3 and BO stretching during the potential drop, it can be seen that BF3 and ether groups are complexed with THP molecules on the negative electrode surface.
[0151] The two peaks are not observed in the electrolyte without LiBF4. Fig.14b Support them from BF3 - The SERS activity of BF3-THP was reduced by the BF4 complexation reaction of BF3-THP and THP. Subsequently, if the potential exceeds 0 V and Li is electrodeposited on Ag, the surface signal of BF3-THP at the electrode decreases, and the signal of the bulk electrolyte (THP) increases due to the reduction of SERS activity. Nevertheless, the signal of BF3-THP was continuously observed on the surface of the lithium precipitate during lithium plating. Although it is known that LiBF4 is usually converted to BF3 by thermal decomposition, the SERS results show that BF3-THP can be formed on the electrode surface with lower potential of pyran solvent even at room temperature.
[0152] In Figure 3, DFT calculations were performed to study the formation of BF3-THP on the Li0 surface in pyran solvent. The activation energy barriers of the BF3 complexation reaction are 1.98 eV and 1.92 eV for THP and THF molecules, respectively, and the reaction enthalpies are 1.02 eV and 0.96 eV, respectively.
[0153] In the case of ethylene carbonate (EC), BF3 did not form a stable adduct, but existed as free BF3 in an sp2 hybridized structure with a reaction enthalpy as high as 1.76 eV. This result indicates that the BF3 complexation reaction is more likely to occur in ether solvents. This is because the energy of BF3 can be stabilized by the cationic bonding between the boron and ether groups of BF3 ( Fig.15 ).
[0154] However, THP has a lower endothermic reaction enthalpy than carbonate solvents, but the predicted equilibrium constant ( , ignoring the entropy term at room temperature) is 5.62×10 -18, therefore, the concentration of BF3-THP in the bulk electrolyte is expected to be very low, which can be confirmed by the absence of BF3-THP signal before the potential drop in the SERS experiment (in situ SERS). Importantly, the complexation reaction of BF3 and THP is likely to occur on the Li0 surface, which exhibits an activation barrier of 1.23 eV and a reaction enthalpy of 0.30 eV. Assuming a predicted equilibrium constant of 8.44×10 -6 , and the activity of the solid LiF precipitate is consistent with the reaction of LiBF4↔LiF+BF3, the concentration of BF3-THP at the Li electrode is calculated to be about 0.5 ppm. Such calculation results support the observation of BF3-THP signal on the low-potential negative electrode surface.
[0155] The density of states (DOS) shows that the F - The 2p orbital of Li0 moves below the Fermi level ( Fig.16 ). This shows that F - The 2p orbital of accepts electrons from Li0. In other words, it can be seen that the positively charged Li0 donates electrons to the negatively charged F atoms, thereby reducing the activation barrier and reaction enthalpy. Different from the bulk LiBF4 / THP electrolyte, when THP is applied, it is expected that the F atoms on the Li0 surface - The energy stabilization of BF3 plays an important role in promoting the BF3 complex reaction on the Li0 surface. It is generally known that BF3 adducts react with fluoride salts, and in this specification, the effect of BF3 adducts on LiF crystals is studied. A 1M solution of LiF in BF3-THF is completely transparent and yellow, while LiF is not completely soluble in common organic solvents ( Fig.17 ).
[0156] pass 11 B NMR observation of the state of boron in the LiF solution of BF3-THF confirmed that as the LiF concentration increased, the amount of BF3-THF decreased and the amount of LiBF4 increased ( Figure 3c and Figure d). This indicates that BF3-THF reacts with LiF to be converted into LiBF4.
[0157] The LiF solution of BF3-THF showed 10 -1 ~10 -2 mxD -2 The ionic conductivity ( Figure 3e ), while 1 M LiF DME, THF, and THP showed two times lower ionic conductivity, indicating that BF3-THF and LiF have been converted into free LiBF4.
[0158] exist Figure 3bIn the energy diagram of , the reaction of BF3 + LiF → LiBF4 is more exothermic at the bulk THP than at the Li0 surface, and therefore, it can be expected that LiF in the external SEI is thermodynamically easier to dissolve than near the Li0 surface.
[0159] Based on the formation of BF3-THP on Li0 and the regeneration of LiBF4, Figure 3f The LiF reconstruction in borate-pyran electrolytes can be understood by the mechanism in . Specifically, an initial SEI containing LiF particles is formed on Li0, and Li passivation is not yet complete in the initial stage, so that LiBF4 and THP are able to contact the Li0 surface. BF3-THP is formed on the surface of Li0 to precipitate LiF on Li0, and BF3-THP reacts with the initial LiF particles and converts back to LiBF4. LiBF4 precipitates LiF again at the location where Li0 is exposed, while forming BF3-THP. By repeating this process, as seen in cryo-TEM observations, the initial LiF particles in the SEI are reconstructed in a way that gradually blocks the new Li0 surface, and eventually the Li surface is passivated into fine LiF crystals.
[0160] Experimental Example 3: Analysis of Li morphology and Coulombic efficiency
[0161] The boron fluoride-cyclic ether electrolyte is compared with a conventional carbonate electrolyte (1 M LiPF6EC / EMC 1:1 vol / vol + 2% VC) and a local high concentration electrolyte (LHCE, 1.5 M LiFSI DME / TTE, 22:78 vol / vol 10) to investigate the morphology of Li precipitates, Coulombic efficiency / inefficiency, and corrosion.
[0162] The morphology of the lithium precipitate was confirmed by applying a pressure of 290 kPa to the bolt fixture using a custom-made pressure fixture ( Figure 4a and 18 ). The lithium deposited in the three electrolytes showed a shiny silver color with no significant differences when observed with the naked eye. However, SEM observations showed more moss-like morphology on the lithium deposited in the conventional carbonate electrolyte. In the other two electrolytes (LHCE and borate-pyran electrolyte), dendrite-free Li with a diameter of about 3 μm was observed. In particular, LHCE and borate-pyran electrolytes formed dense and uniform cross-sectional lithium morphology. This dense morphology was not observed in the LiTFSI THP:FEC electrolyte ( Fig.19 ).
[0163] The Coulombic efficiency of lithium plating / stripping on copper and lithium metal substrates was measured. Figure 4b For carbonate electrolytes, LHCE, and borate-pyran electrolytes, the first cycle (0.5 mA cm-2 and 5mAh cm -2 ) coulombic efficiencies are about 98.8%, 96.9%, and 99.3%, respectively. In particular, it is found that the one-cycle coulombic efficiency of the carbonate electrolyte is higher than that of the LHCE, presumably because the efficiency of the carbonate electrolyte with relatively poor Li morphology can be greatly improved under uniform pressure.
[0164] The boron fluoride-cyclic ether electrolyte showed a Li cycle efficiency of 99.33% and 99.42% in the first and second cycles on a Cu substrate, respectively. Then, the average efficiencies on a Li substrate obtained by the modified Aurbach method were 88.14% and 99.62% for carbonate electrolytes and LHCE electrolytes, respectively. In the case of LHCE electrolytes, the Li cycle efficiencies measured by the Aurbach method for recently reported LHCE or fluorine-based solvent electrolytes showed similar values to the results (99.5% to 99.6%). The average efficiency of the boron fluoride-cyclic ether electrolyte was 99.85%, which is one of the highest values among non-aqueous electrolytes known to date.
[0165] In order to understand the cause of the Coulomb inefficiency in the lithium plating / stripping process, titration gas chromatography (TGC, Fig. 20 ) to quantify lithium loss pathways.
[0166] exist Figure 4c The total cumulative capacity, the sum of the cumulative losses, and the dead Li0 and SEI Li are plotted by applying the Aurbach method and then TGC. + The carbonate electrolyte and LHCE formed SEI with 6.65% and 0.71% of the total cumulative capacity using Li source, respectively.
[0167] Unlike the other two electrolytes, the borate-pyran electrolyte shows less Li loss due to SEI formation (0.23% of the total cumulative capacity) than the formation of dead Li0. This indicates that the borate-pyran electrolyte has lower Coulombic inefficiency for SEI formation compared with conventional carbonate electrolytes and LHCE systems.
[0168] By measuring the time-dependent interfacial resistance (R 界面 ) to confirm the corrosiveness of the electrolyte. Figure 4d It is shown that the initial interfacial resistance and its change with aging time are different for each electrolyte. The conventional carbonate electrolyte shows the highest R 界面 (100~250Ω cm -2 ), which indicates that the SEI component formed in the carbonate electrolyte has a higher resistance than that formed in the ether electrolyte.
[0169] In the initial state, LHCE shows a higher -2 )Higher 40Ω cm -2 R 界面 , and increased to 245Ω cm after aging for 5 days -2 , while the boron fluoride-cyclic ether electrolyte only showed 31Ω cm even after aging for 5 days. -2 .
[0170] In particular, such low interfacial resistance values were not observed in the absence of LiBF4. By observing the normalized resistance, the extent of long-term corrosion of lithium and electrolyte due to aging can be clearly compared.
[0171] The LHCE system with high corrosion showed the fastest SEI growth, with R 界面 The R of the borate-pyran electrolyte increased by 6 times during aging for 5 days, which is about twice that of conventional carbonate electrolytes or LiTFSI THP:FEC electrolytes. 界面 It only increased by 23%. The electrolyte without LiBF4 (LiTFSI THP:FEC) did not show such a low SEI growth rate. It can be seen that reconstructing LiF by LiBF4 in boron fluoride-cyclic ether electrolyte can reduce the SEI increase rate.
[0172] The corrosion rate of electrodeposited Li in the electrolyte is quantified by the time-dependent CE loss as well as the intrinsic corrosivity of the electrolyte, where CE is affected by the surface area (i.e., morphology, Figure 4e ). In the case of aging for 5 minutes after initial lithium plating followed by lithium stripping, a CE of 96.5% was observed for LHCE, 96.9% for borate pyran electrolyte, and 85% for conventional carbonate electrolyte in a coin cell configuration.
[0173] During the 2-day aging period, the CE losses of the conventional carbonate electrolyte and LHCE were shown to be 10.7% and 4.70%, respectively, indicating that both the low-CE electrolyte and the high-CE electrolyte were involved in significant lithium corrosion during aging. The CE loss of the boron fluoride-cyclic ether electrolyte during aging for 2 days was shown to be only 1.02%, and a long-term CE loss of 3.86% after 10 days, 6.56% after 21 days, and 14.9% after 3 months was shown, which is much lower than that of other electrolyte systems ( Fig.21 ). This mitigation of CE loss was not observed when LiBF4 was not included in the electrolyte.
[0174] The average corrosion rate during each period is Figure 4fThe carbonate electrolyte showed >3.5 μAh h at a maximum of 24 h. -1 The high corrosion rate of LHCE is probably due to the large surface area of lithium precipitates. The EIS results show that LHCE is more corrosive than carbonate electrolytes, but due to the low surface area of deposited Li, the corrosion rate is 0.8 μAh h -1 , which is lower than the corrosion rate of carbonate electrolyte.
[0175] The boron fluoride-cyclic ether electrolyte showed a peak value of about 0.1 μAh h after 120 h. -1 The low corrosion rate of LHCE and the Li deposited in the boron fluoride-cyclic ether electrolyte showed almost the same dense morphology in the SEM images, indicating that the boron fluoride-cyclic ether electrolyte has a high passivation due to this low corrosion rate.
[0176] It is therefore predicted that boron fluoride-cyclic ether-based electrolytes will be able to minimize electrolyte molecule loss and lithium loss due to SEI formation on electrodeposited lithium or self-corrosion of dead LiO that gradually develops over the life of the battery.
[0177] Experimental Example 4: Performance of Li||NCM811 under harsh conditions
[0178] Relative to Li / Li + , boron fluoride-cyclic ether electrolytes have an oxidative stability of about 5 V, which corresponds to the electrolyte requirements for driving LMBs based on >4 V anodes.
[0179] Linear sweep voltammetry (LSV) measurements of several electrolytes confirmed a general trend: the co-presence of FEC and LiBF4 can increase the oxidative stability of ether solvent-based electrolytes.
[0180] Double-sided coated NCM811 (18.78 mg cm -2 、3.89 mAh cm -2 ) is paired with a Li negative electrode (40 μm, N / P ratio 2.08) in a pouch-type full cell ( Figure 5a ), and if Figure 5b The two volume factors using injected liquid electrolytes are shown. Although 1.82 g Ah is smaller than the state-of-the-art LMBs reported to date, -1 The value is a lower E / C ratio, but it means that even after filling the battery pores, the volume of injected liquid is much larger than that of ordinary LIBs.
[0181] To confirm that the corrosion of the electrolyte can be reduced to drive very dilute electrolyte LMB (E / C about 1 g Ah -1 ), and also evaluated the E / C ratio of 1.18 g Ah -1The estimated energy density is 1.82 g Ah at E / C based on these cell parameters. -1 424 Wh kg -1 , at E / C 1.18 g Ah -1 456 Whkg -1 (Table 1).
[0182]
[0183] The voltage curves of pouch cells prepared with three electrolytes were studied based on the battery capacity and specific capacity ( Figure 5c ). Boron fluoride-cyclic ether electrolytes show specific capacities during 1C, 2C, and 3C discharges, respectively. Boron fluoride-cyclic ether electrolytes have high ionic conductivity (0.35Ω cm -2 , including the separator) and low interfacial resistance, which contributes to high-rate performance.
[0184] In summary, this paper provides a boron fluoride-cyclic ether electrolyte for LMB. The boron fluoride-cyclic ether electrolyte has low corrosion and reconstructs a fine passivation lithium electrolyte interface through LiF, thereby minimizing the Coulomb ineffectiveness of SEI formation on lithium. In addition, the boron fluoride-cyclic ether electrolyte shows an ideal lithium deposition form and high lithium plating / stripping efficiency (average CE of 99.86%), and meets the conditions required for long-term operation of LMB at low N / P and E / C ratios.
[0185] In particular, the Ni-rich NCM811 cathode (3.83 mAh cm -2 ) and thin Li anode (N / P 2) showed a high efficiency at 1.82 g Ah -1 (424 Wh kg -1 ) for more than 500 cycles at E / C and at 1.18 g Ah -1 (456 Whkg -1 ) at an E / C of 250+ cycles and high energy density, which mitigates the irreversibility caused by the corrosiveness of the electrolyte, thus achieving a high energy density at less than 2 g Ah. -1 Long-cycle LMB under the conditions of .
Claims
1. An electrolyte composition comprising: an ether solvent having an ether group; and a boron fluoride lithium salt or a non-boron fluoride lithium salt dissolved in the ether solvent, The boron fluoride lithium salt or the non-boron fluoride lithium salt forms a complex with the ether solvent.
2. The electrolyte composition according to claim 1, wherein the boron fluoride lithium salt comprises a boron fluoride lithium salt of the following formula 1: [Formula 1] LiBF x R y in, R is -CF3 or -styrene, and x+y=4. The electrolyte composition according to claim 1 , wherein the ether-based solvent is a cyclic ether-based solvent. 4 . The electrolyte composition according to claim 1 , wherein the ether solvent has one ether group. 5 . The electrolyte composition according to claim 1 , wherein the boron fluoride-based lithium salt and the ether-based solvent form a boron trifluoride-ether complex. 6 . The electrolyte composition according to claim 1 , wherein the non-fluoride boron-based lithium salt comprises an anion-based lithium salt having a Group 13 element as a central atom, or a lithium salt consisting of a boron central atom and a halide-based anion other than fluorine. 7 . The electrolyte composition according to claim 1 , wherein the ether solvent comprises at least one solvent selected from the group consisting of tetrahydrofuran (THF), tetrahydropyran (THP), furan, pyran, ethylene oxide, oxetane, oxepane, and dioxane.
8. The electrolyte composition according to claim 2, wherein the boron fluoride-based lithium salt is LiBF4, and the ether-based solvent is tetrahydropyran (THP).
9. The electrolyte composition according to claim 1, The invention further comprises at least one selected from the group consisting of an ion-conductive lithium salt and an additive.
10. The electrolyte composition according to claim 9, wherein the ion-conductive lithium salt comprises at least one lithium salt selected from the group consisting of LiTFSI, LiFSI, LiBETI, LiAsF6, LiPF6, LiSbF6, LiDFOB and LiBOB, and The additive includes at least one additive selected from the group consisting of FEC, DFEC, TFEC, TFTFE, TTE, BTFE, OFE and TFOFE.
11. The electrolyte composition according to claim 10, wherein the ion-conductive lithium salt is LiTFSI, and The additive is FEC which acts as a LiF former.
12. The electrolyte composition according to claim 9, wherein the anion of the ion-conductive lithium salt has a lower Li + Binding energy. 13 . The electrolyte composition according to claim 2 , wherein the electrolyte composition has a BO stretching signal and a FBF bending signal in SERS analysis.
14. A lithium metal battery comprising: The electrolyte composition according to any one of claims 1 to 13; A negative electrode comprising a lithium metal film formed on a negative electrode current collector; a positive electrode comprising a positive electrode active material layer formed on a positive electrode current collector; and A separator is formed between the negative electrode and the positive electrode. 15 . The lithium metal battery according to claim 14 , wherein the boron fluoride-based lithium salt and the ether-based solvent form a boron trifluoride-ether complex on the surface of the lithium metal thin film.
16. The lithium metal battery according to claim 14, further comprising a SEI layer formed on the lithium metal film, The SEI layer has only signals of LiF (111) or LiF (220) grids in a fast Fourier transform (FFT) image.
17. The lithium metal battery according to claim 14, wherein the SEI layer is passivated into LiF crystals by a reconstruction process in which BF3-THP is formed on the lithium metal film and LiF is precipitated on LiO.
Citation Information
Patent Citations
Vaporizer for semiconductor process using carrier gas
KR1020220105317A
Dual-Band Reconfigurable-Polarization Phase Array Antenna System
KR1020230103596A